2013
DOI: 10.1074/jbc.m113.500983
|View full text |Cite|
|
Sign up to set email alerts
|

Triptolide-induced Cell Death in Pancreatic Cancer Is Mediated by O-GlcNAc Modification of Transcription Factor Sp1

Abstract: Background: Preclinical evaluation of triptolide shows pancreatic tumor regression in animal models. Results: Triptolide deregulates glycosylation of Sp1, leading to its decreased activity and causing pancreatic cancer cell death associated with down-regulating HSP70. Conclusion: Triptolide down-regulation of HSP70 is associated with inhibition of Sp1 activity in pancreatic cancer. Significance: This mechanism is of relevance, as its water-soluble prodrug, Minnelide, is currently under Phase 1 clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 37 publications
3
69
0
Order By: Relevance
“…Our more recent study explored this further and showed that triptolide inhibits the transcription factor Sp1, which is upstream of a number of signaling pathways (4). This study further shows that HSF1, the transcription factor for HSP70, and NF-B, the transcription factor for a number of ER stress genes including GRP78, are regulated by Sp1.…”
Section: Discussionmentioning
confidence: 96%
“…Our more recent study explored this further and showed that triptolide inhibits the transcription factor Sp1, which is upstream of a number of signaling pathways (4). This study further shows that HSF1, the transcription factor for HSP70, and NF-B, the transcription factor for a number of ER stress genes including GRP78, are regulated by Sp1.…”
Section: Discussionmentioning
confidence: 96%
“…Stabach et al proved that overexpression of AP2α could alter the transcriptional activity and stability of p53 in tumor tissue [43]. Besides, the nuclear localization of SP1 and its DNA binding activity could be suppressed by the inhibition of O-GlcNAc transferase, and then functioned in the cell death of pancreatic cancer [44]. Also, SP1 was a key modulator of p53-mediated apoptosis in cell apoptosis [45].…”
Section: Discussionmentioning
confidence: 97%
“…Triptolide supresses the proliferation of prostate cancer cells by inhibition of expression of SUMO-specific protease 1 (7). Triptolide induces the apoptosis of pancreatic tumor cells by decreasing the expression of O-GlcNac transferase to alter the distribution of transcription factor specificity protein 1 (8). However, it is not clear if triptolide can be used to treat osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%